Correction: Factors affecting forest area change in Southeast Asia during 1980-2010. - Nobuo Imai; Takuya Furukawa; Riyou Tsujino; Shumpei Kitamura; Takakazu Yumoto (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0197391.].